Narcissistic Leadership at Workplace and the Degree of Employee Psychological Contract: A Comparison of Public and Private Sector Organizations in Pakistan - Malik, Kamran; Khan, Fouzia Naeem (International Journal of Economics, Business and Management Studies, 2013)
This research was conducted to study the effects of Narcissistic leadership displayed in the public and private sector of Pakistan. Leadership style is of utmost importance at the workplace. It’s a frequent observed phenomenon in corporate world that employers develop a great degree of Narcissism i.e. self admiration among themselves. Subsequently this narcissistic leadership style manifests into certain negative behaviours as defensiveness, mistrusting others, paranoia, self promotion, indifference etc. which not only undermines his/her leadership effectiveness but also have grave effects on employees. As a result, there is a phenomenal reduction in the components of employees’ psychological contract. Although there have been numerous international studies on narcissistic leadership highlighting what constitute as narcissistic behaviours in employers and their impact on employee’s psychological contract yet such comprehensive studies in the local corporate context have been missing. This research aimed at identifying; what percentage of Pakistani bosses, in our sample, from within the banking sector, exhibit narcissism, what are the behavioural manifestations of this narcissism, what percentage of bosses display narcissistic behaviours at work and to what degree, and what is the impact of such boss behaviours on employee’s psychological contract. For this purpose a questionnaire was designed and data was collected from a sample of 96 people within various public and private sector organizations. Four hypotheses were developed and tested through regression analysis. Various other statistical techniques including demographical analysis, reliability analysis and correlations were also employed for data analysis. The survey findings show strong correlations between determinants of narcissistic leadership and components of employee psychological contract. It brings a comprehensive insight as how boss’s narcissism hurts the employees and ultimately the organizations. The comparison of public and private sector in this regard does not show any considerable variations. The research concludes with various ways of shaping organizational climate and enhancing workplace sanity. In the end, certain recommendations are included which highlight different designs of measuring and channelizing narcissism among bosses.